Optimization of the CRISPR/Cas9 System to Manipulate Gene Function in Rhizopus delemar. (4th October 2017) - Baldin, Clara; Soliman, Sameh; Jeon, Heewon; Skory, Christopher; Edwards, John; Ibrahim, Ashraf
Abstract: Background: The genus Rhizopus is the main cause of mucormycosis, a life-threatening infection that affects predominantly hosts with an impaired immune system. However, patients with severe trauma and burns, without prior immune deficiency, are also at increased risk of developing mucormycosis. Despite aggressive treatment that involves disfiguring surgery and antifungal therapy, mortality rates range from ~50 to 100%. Genetic manipulation of Rhizopus is critical for identifying fungal targets to develop more effective therapies. However, Rhizopus genetics are challenging because of lack of dominant selection markers, low efficiency of transformation, and rarity of chromosomal integration. Here we attempted to adapt the CRISPR/Cas9 technology to disrupt genes in R. delemar . Methods: We used the Gibson cloning strategy to assemble all necessary elements of the CRISPR/Cas9 system in one plasmid using the pyrF as a selection marker. The targeted gene for disruption was a toxin-encoding gene with similarity to ricin. This disruption cassette was transformed using biolistic delivery system into R. delemar pyrF - strain (M16). Recombination events were studied by Southern blot analysis and ricin gene expression was analyzed by qRT-PCR. Furthermore, damage to alveolar epithelial cells (A549) and nasal epithelial cells (CCL30) was studied with 51 Cr-release assay. Results: Five stable transformants were obtained with the CRISPR/Cas9 construct. Southern blot analysis and nucleotide sequencing confirmed a partial deletion of the ricin gene, in the region where the guide RNA was designed. Moreover, gene disruption was confirmed by abrogation of ricin expression in comparison to reference strains (wild type or mutant with the CRISPR/Cas9 plasmid void of ricin gene sequence). Finally, ricin-mutants showed significant reduction in damage to A549 cells and CCL30 cells when compared with the reference strains (20–30% reduction, P < 0.01 by t -test). Conclusion: We have successfully adapted the CRISPR/Cas9 system to disrupt the ricin-like gene in R. delemar. This tool will enable us to better understand the pathogenesis of mucormycosis and ultimately aid in designing novel and more successful strategies to manage this lethal fungal infection. Disclosures: All authors: No reported disclosures.